Endocarditis due to Aggregatibacter Segnis: a rare case report - Xiaoxiao Guo; Xinyun Zhang; Yanli Qin; Hong Liu; Xinyu Wang (BMC Infectious Diseases, 2023)
Abstract Background As a member of the HACEK group, Aggregatibacter segnis (A. segnis) is a fastidious Gram-negative coccobacillus that resides in the human oropharyngeal flora. Infective endocarditis caused by A. segnis is rarely reported. Case presentation A 31-year-old male was admitted to our hospital for a 3-month history of intermittent high fever, chills, and chest distress. On presentation, he was febrile and tachycardic but otherwise with stable vital signs. Physical examination revealed systolic murmurs in the aortic and mitral valve areas. Pitting edema was evident in the lower extremities. Transthoracic echocardiography demonstrated multiple vegetations in the mitral and aortic valves. Severe regurgitation of the aortic valve and left heart dysfunction were also detected. With the suspicion of infective endocarditis and heart failure, we immediately performed microbiological tests and arranged the cardiac replacement surgery. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry and metagenomic next-generation sequencing (mNGS) identified A. segnis from the bloodstream. While the surgical specimen culture was negative, the mNGS was positive for A. segnis. The patient was treated with ceftriaxone for four weeks and discharged. He remained clinically well, with laboratory results restored. Conclusion This is the first report of A. segnis infective endocarditis that combined MALDI-TOF and metagenomic next-generation sequencing in the diagnosis. The hypothesis-independent molecular techniques can outperform conventional tools to prevent diagnostic delay.